Work-to-family effects of inclusive leadership: The roles of work-to-family positive spillover and complementary values - Zhu, Hong; Chen, Amy Y. Y. (Frontiers in Psychology, 2022)
Drawing on family enrichment theory, we explore how and when inclusive leadership affects employees’ family performance by investigating the mediating role of work-to-family positive spillover and the moderating role of complementary values. A time-lagged study was conducted and the sample included 292 employees from two hotels. The results indicate that inclusive leadership is indirectly associated with employees’ family performance via work-to-family positive spillover, and that employees’ complementary values may strengthen the positive effect of inclusive leadership. We also provide theoretical and practical implications of the results.